PENENTUAN KEPUTUSAN INVESTASI SAHAM DENGAN PENDEKATAN SINYAL BELI DAN SINYAL JUAL PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA LQ 45 - Kostini, Nenden; Sukmadewi, Rani; Fahmi, Muhammad Ainul (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2023)
This research aims to determine the use of technical analysis as a basis for investors' considerations in making investment decisions in shares of banking sector companies registered on LQ 45 in 2018. The research method uses a quantitative approach by processing secondary data obtained from the results of further processing by primary data collectors. Technical analysis is used to analyze stock price movements using Moving Average Convergence Divergence (MACD) and RSI as indicators. The research population is banking sector companies listed on the Indonesia Stock Exchange (IDX) as many as 590 companies while the sample size is determined by purposive sampling, namely banking companies belonging to the LQ 45 index for the period February - July 2018 as many as 6 banking sector companies. The unit of analysis of this research is stock price data of companies in the banking sector. The results of data analysis show